2019
DOI: 10.37694/jwp.v15i1.30
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH LAMA FERMENTASI TERHADAP MUTU TEPUNG UBI JALAR (Ipomea batatas L.) BERBAGAI WARNA UMBI

Abstract: The usage development can be increased by applying right cultivating and processing technology to grow sweet potato agroindustry that can help increasing economy value and lengthening storability. One of sweet potato potencies that can be developed in food diversification is sweet potato flour processing. The objective of this research is to study about the effect of fermentation time and various color of sweet potato to the quality of sweet potato flour. The research was done on April until June 2015 in Basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Aisah et al (2021) reported that a decrease in fat content was possible during the fermentation process, as microbes required energy obtained from fat. Based on the results, MOCAF sample's fat content met the SNI 7622-2011 required quality standards, with a maximum value of 0.806% (Iswari et al, 2016).…”
Section: Mocaf Proximate Testmentioning
confidence: 88%
“…Aisah et al (2021) reported that a decrease in fat content was possible during the fermentation process, as microbes required energy obtained from fat. Based on the results, MOCAF sample's fat content met the SNI 7622-2011 required quality standards, with a maximum value of 0.806% (Iswari et al, 2016).…”
Section: Mocaf Proximate Testmentioning
confidence: 88%
“…Lamanya waktu fermentasi memberikan pengaruh terhadap derajat putih tepung mocaf yang dihasilkan, hal ini disebabkan adanya degradasi senyawa kompleks oleh mikroba selama proses fermentasi sehingga pigmen pada ubi kayu terurai dan larut dalam air. Selain itu, proses fermentasi pada ubi kayu ternyata dapat menghambat reaksi maillard yang menyebabkan produk menjadi berwarna kecoklatan (Iswari et al, 2010). Dengan cara merombak gula pereduksi menjadi asam-asam organik (Putri et al, 2018).…”
Section: Analisis Derajat Putihunclassified
“…Derajat putih merupakan kemampuan suatu bahan untuk memantulkan cahaya yang mengenai permukaan bahan tersebut (Iswari et al, 2016). Data rata-rata derajat putih tepung sagu "Dwitrap" dapat dilihat pada Tabel 2.…”
Section: Derajat Putihunclassified